Performance and characteristics of Piau’s carcass - Moreira, Amaury C. de Souza; Peloso, Vicente de P. Mendes; Alvarenga, Julio Calvelli; Lima, Therezinha de A. Oliveira; Rocha, Mércia de Andrade; Costa, Francisco Ademar; Villar, Manuel C. Carballo (Pesquisa Agropecuaria Brasileira, 2014)
The performance and characteristics of carcass were studied in Piau's race. The experiment was carried out with 20 hogs, divided in five treatments, with four repetitions. The most important obtained results were: a) days to reach 90 kg; b) daily gain, 0.469 kg; c) weight of the cooled carcass 71.348 kg; d) length of the cooled carcass 69.48 cm; e) lard thickness 5.39 cm; f) total of prime cuts in relation to the cooled carcass 32.82% and 26.93% with respect to the living weight, and g) loin-oye area between the 10 th and the 11 th ribs 18.12 cm2. The results obtained by the "t" test demonstrate that the general characteristics of the carcass and the percentages of the prime cuts, related to the live weight and to the carcass, were inferior to the pig meat type, with highly significant differences (with exception of the length of the carcass).